Effect of methylprednisolone on experimental brain edema in rats - own experience reviewed - Kozler, Petr; Marešová, Dana; Pokorný, Jaroslav (Physiological research, 2021)
Brain edema - a frequently fatal pathological state in which brain volume increases resulting in intracranial pressure elevation - can result from almost any insult to the brain, including traumatic brain injury. For many years, the objective of experimental studies was to find a method to prevent the development of brain edema at the onset. From this perspective, the use of methylprednisolone (MP) appears promising. High molecular MP (MW>50 kDa) can be incorporated into the brain - in the conditions of the experimental model - either by osmotic blood-brain barrier disruption (BBBd) or during the induction of cellular edema by water intoxication (WI) - a condition that increases the BBB permeability. The time window for administration of the MP should be at the earliest stages of edema. The neuroprotective effect of MP on the permeability of cytoplasmatic membranes of neuronal populations was proved. MP was administrated in three alternative ways: intraperitoneally during the induction of cytotoxic edema or immediately after finishing cytotoxic edema induction in a dose of 100 mg/kg b.w.; into the internal carotid artery within 2 h after finishing cytotoxic edema induction in a dose of 50 mg/kg b.w.; into internal carotid artery 10 min after edema induction by BBBd in a dose of 50 mg/kg b.w.
Keywords: Animals; Rats, Wistar; kapilární permeabilita; Brain Edema; glukokortikoidy; Glucocorticoids; neurony; Blood-Brain Barrier; mozek; hematoencefalická bariéra; Neurons; Male; Capillary Permeability; modely nemocí na zvířatech; Neuroprotective Agents; Brain; Methylprednisolone; edém mozku; methylprednisolon; Disease Models, Animal; krysa rodu Rattus; zvířata; mužské pohlaví; Rats; potkani Wistar; neuroprotektivní látky